2015
DOI: 10.1080/00380768.2015.1049930
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of N2O emissions to the abundance of soil ammonia oxidizers and denitrifiers in purple soil under long-term fertilization

Abstract: Microbial nitrification and denitrification are responsible for the majority of soil nitrous (N 2 O) emissions. In this study, N 2 O emissions were measured and the abundance of ammonium oxidizers and denitrifiers were quantified in purple soil in a long-term fertilization experiment to explore their relationships. The average N 2 O fluxes and abundance of the amoAgene in ammonia-oxidizing bacteria during the observed dry season were highest when treated with mixed nitrogen, phosphorus and potassium fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…+ and NO 3 − concentrations after mineral N fertilizer application to the croplands (Figure 3a,b). The high NH 4 + and NO 3 − concentrations following fertilization directly provide sufficient substrates for nitrification and denitrification and thus significantly stimulate soil N 2 O emissions [8,11,20,23]. This phenomenon has been reported in many previous studies on different croplands [5,10,43].…”
Section: Factors Regulating the Increased Soil N 2 O Emissions Inducesupporting
confidence: 53%
See 3 more Smart Citations
“…+ and NO 3 − concentrations after mineral N fertilizer application to the croplands (Figure 3a,b). The high NH 4 + and NO 3 − concentrations following fertilization directly provide sufficient substrates for nitrification and denitrification and thus significantly stimulate soil N 2 O emissions [8,11,20,23]. This phenomenon has been reported in many previous studies on different croplands [5,10,43].…”
Section: Factors Regulating the Increased Soil N 2 O Emissions Inducesupporting
confidence: 53%
“…On the other hand, good soil aeration condition accelerated the gas exchange between soil and atmosphere, which could promote the diffusivity of N 2 O from soil into atmosphere [3,14]. Application of mineral N fertilizer could directly increase soil inorganic N concentrations (Figure 3), providing substrates for the two main N 2 O production processes of nitrification and denitrification [8,9,28]. In this study, the N 2 O flux from the croplands all showed pulse emissions following tillage and N fertilization events (Figure 4a), thus resulted in much greater cumulative N 2 O emissions compared to the forestland (Table 3).…”
Section: Effects Of Land Use Conversion On Soil N 2 O Emissions and Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, there is no dominant driver connected to variations of different microbial communities across the crop systems.Then, we can argue that better understanding of the link between the most significant drivers with the microbial community across the crop systems may be achieved using mathematical modeling based on ecological theories (see Wade et al, 2016;Prosser et al, 2007). The application of nitrogen, phosphorus and potassium fertilizer increased the N 2 O emission (Dong et al, 2015) Wheat…”
Section: The Relevance Of Microbial Community For Soilsmentioning
confidence: 99%